Research on the Integration of Confucian Culture into Life Education of College Students: Take Chinese Perspective - Lingmin Zhang (Journal of General Education and Humanities, 2023)
The splendid Chinese culture has a long history of five thousand years. Confucian culture implications explore regular, seeking truth, sincere attitude, and inner justice; managing the family, governing the state, and benefiting the world; respecting nature, conforming to nature, protecting nature, and returning to nature; loving the motherland, mind the world, and shared destiny of life concept has nourished millions of Chinese people, and also provided a positive educational enlightenment for the life education of college students under the epidemic prevention and control. It draws an important conclusion that it is necessary to strengthen the life education of college students by integrating the Confucian life culture. Then it analyzes the elements of life education and discusses the life thought contained in Confucian culture. Finally, it explores integrating Confucian life culture into college students' life education. This study aims to innovate and carry forward the excellent traditional Chinese culture to promote college students to become gentlemen (junzi).